2017
DOI: 10.1088/1757-899x/200/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

The impact of overhead lines for employees with stents

Abstract: Abstract. The aim of article is to discuss interaction between stents implanted in the body of worker and harmonic magnetic field in the vicinity of electric wires. In last decades, a growing proportion of people has any devices implanted, to list: cardiac pacemakers, cardioverterdefibrillators. Recommendations of International Commision on Non-ionizing Radiation Protection (ICNIRP), and resctrictions imposed in different states, may exlude specific individuals from their duties. The autors focused on the situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Study [4] has shown that short-term exposure to a high voltage power and low frequency environment poses a threat to kidneys of rats. In [5], the authors have shown that if there is a safe distance for employees with stents implanted in the body, the interaction of the line on the stent is negligible. Paper [6] assessed the safety of pectus patients with a concave Nuss bar-implant exposed to a plane wave with a frequency of 64 MHz, using the finite-difference time-domain (FDTD) method.…”
Section: Introductionmentioning
confidence: 99%
“…Study [4] has shown that short-term exposure to a high voltage power and low frequency environment poses a threat to kidneys of rats. In [5], the authors have shown that if there is a safe distance for employees with stents implanted in the body, the interaction of the line on the stent is negligible. Paper [6] assessed the safety of pectus patients with a concave Nuss bar-implant exposed to a plane wave with a frequency of 64 MHz, using the finite-difference time-domain (FDTD) method.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the induction of eddy currents in metal implantable devices under RF fields [Sawicki et al, 2006;Ye et al, 2015]. Both the passive implants, such as vascular stents [Syrek et al, 2017], metal bar-implants [Miaskowski et al, 2016], hip and orthopedic implants [Kozlov et al, 2015;Miaskowski et al, 2012], prosthetic and dental implants [Safari et al, 2016], as well as the active implants like pacemakers and cardiac implantable devices [Gniadek-Olejniczak et al, 2018;Smondrk et al, 2018], deep brain stimulators [Guerin et al, 2019], etc., interact with the external EMFs produced by communication systems [Mat et al, 2017;Ye et al, 2015] or strong magnetic gradients generated by modern medical diagnostic tools such as magnetic resonance imaging (MRI) devices [Gniadek-Olejniczak et al, 2018;Yao et al, 2019]. Metal implants often prevent their patients from enjoying the benefits of modern civilization including MRI due to severe interactions with active implantable medical devices (AIMD) or discomfort feeling, pain and burning sensations [Zradzinski et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…Even if numerous studies have been published over the last 25 years related to human exposure to low-frequency electric and magnetic fields [2][3][4][5][6], the possible connection between the magnetic field generated by appliances and the current consumption has not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%